Mapping of Banyuwangi Regency’s Capacity in Implementing Policy for Producer’s Waste Reduction Roadmap - Kuncoroyekti, Andre; Hartati Kartikaningsih; Dini Atikawati (Wacana Journal of Social and Humanity Studies, 2025)
In 2020, Banyuwangi Regency generated 852 tons of waste daily, with 78% (approximately 664 tons) unmanaged, primarily from rural areas (83%). By 2021, about 77% of this waste will continue to pollute the environment, and projections for 2040 indicate annual waste could exceed 500,000 tons, posing a risk of 385,000 tons of environmental pollution without enhanced management strategies. Private sector involvement is mandated by Banyuwangi Regulation No. 6/2022, requiring companies to implement waste reduction initiatives and develop comprehensive waste management plans, necessitating monitoring and evaluation for effective policy implementation. This paper investigates the Banyuwangi Government's capacity to implement waste reduction roadmaps by producers in the Regency.  The study uses a qualitative descriptive method. Data collected consist of secondary and primary data. The study consists of two analyses. The first analysis was conducted on sample documents of waste reduction roadmap developed by producers to assess the document’s quality. The second analysis is to assess the policy capacity of Banyuwangi Regency Environmental Agency to understand which area of competence still needs to be strengthened. The study emphasizes the need for producers to register with the Environmental Agency, ensuring compliance and oversight of waste reduction initiatives. The research highlights the significance of adaptability in the political landscape, particularly in modifying strategies to correspond with shifts in political leadership and development objectives. It also confronts the local government's limited financial capacity. The paper provides initial insights regarding the Banyuwangi local government's capacity to effectively enact these policies. Keywords: waste reduction, policy implementation, government policy capacity